Influence of islamic corporate social responsibility and intellectual capital on firm value, a study of companies listed on the jakarta islamic index for the 2019-2022 period - Saputra, Anggi; Ruslan Abdul Ghofur; Ersi Sisdianto (Central Research Institute for Agriculture (CeRIA), 2024)
This study aims to analyze the effect of Islamic corporate social responsibility and intellectual capital on firm value in 2019-2022. This research uses a case study approach, in this case using companies listed on the Jakarta Islamic Index (JII) for the 2019-2022 period. This research is quantitative research. The population in this study were 48 companies, the sample in this study amounted to 10 companies in 4 years of observation so that the total observation data amounted to 40 samples. The results showed that the Islamic corporate social responsibility variable had a significant negative effect on firm value, intellectual capital had a significant positive effect on firm value. Islamic corporate social responsibility and intellectual capital variables simultaneously have an influence on firm value in companies listed on the Jakarta Islamic index (JII).